Vaginal sheets with Thymbra capitata essential oil for the treatment of bacterial vaginosis: design, characterization and in vitro evaluation of efficacy and safety - Tomás, Mariana; Sousa, Lúcia Filipa Guimarães Vieira; Oliveira, Ana Sofia; Gomes, Carolina P.; Palmeira-de-Oliveira, Ana; Cavaleiro, Carlos; Salgueiro, Lígia; Cerca, Nuno; Martinez-de-Oliveira, José; Palmeira-de-Oliveira, Rita (Gels, 2023)
We aimed to incorporate Thymbra capitata essential oil (TCEO), a potent antimicrobial natural product against bacterial vaginosis (BV)-related bacteria, in a suitable drug delivery system. We used vaginal sheets as dosage form to promote immediate relief of the typical abundant vaginal discharge with unpleasant odour. Excipients were selected to promote the healthy vaginal environment reestablishment and bioadhesion of formulations, while the TCEO acts directly on BV pathogens. We characterized vaginal sheets with TCEO in regard to technological characterization, predictable in vivo performance, in vitro efficacy and safety. Vaginal sheet D.O (acid lactic buffer, gelatine, glycerine, chitosan coated with TCEO 1% w/w) presented a higher buffer capacity and ability to absorb vaginal fluid simulant (VFS) among all vaginal sheets with EO, showing one of the most promising bioadhesive profiles, an excellent flexibility and structure that allow it to be easily rolled for application. Vaginal sheet D.O with 0.32 µL/mL TCEO was able to significantly reduce the bacterial load of all in vitro tested Gardnerella species. Although vaginal sheet D.O presented toxicity at some concentrations, this product was developed for a short time period of treatment, so this toxicity can probably be limited or even reversed when the treatment ends. This work supported by the Portuguese Foundation for Science and Technology within the research project PTDC/BIA-MIC/28271/2017 under the scope of COMPETE 2020 (POCI-01-0145-FEDER-028271) including an individual scholarship and general funding. This work was also developed within the scope of the CICS-UBI projects UIDB/00709/2020 and UIDP/00709/2020, financed by national funds through the Portuguese Foundation for Science and Technology/MCTES.